A dense structure constructed by flake and spherical aluminum: Simultaneously enhanced anti‐wear and anti‐corrosion properties of epoxy/polytetrafluoroethylene composite coatings. Issue 36 (27th July 2022) - Li, Guihua; Xu, Haiyan; Ma, Yanjun; Wu, Yanping; Chen, Lei; An, Yulong; Zhou, Huidi; Chen, Jianmin
Abstract: The construction of a dense structure of the coatings is the basic guarantee to ensure the good performances of the coatings, and it is also one of the problems faced by the most coatings at present. The present work attempts to build a dense coating structure by introducing flake and spherical aluminum powders into the epoxy/polytetrafluoroethylene composite coatings so as to improve the anti‐wear and anti‐corrosion properties of the coatings. As a result, the coating filled with both flake and spherical aluminum exhibited denser microstructure, which was attributed to the synergistic effect of flake and spherical aluminum particles. Among them, the flake aluminum blocked the straight‐through holes in the coating, while the spherical aluminum further filled the micropores between the flake aluminum and the gaps between the flake aluminum and the matrix. In response, the micro‐hardness of the coating was increased by 58.6% and the wear rate was reduced by 80% compared to that of coating without aluminum powders. The excellent wear resistance was attributed to the synergetic effect of the enhanced micro‐hardness of the coating and the formed high load‐bearing tribofilm on the dual ball. Moreover, the coating still maintained the maximum R c of 3.63 × 10 9  Ω cm 2 after 360 h of immersion owing to the improved barrier properties of the coating. Abstract : We develop a flake and spherical aluminum reinforced epoxy/polytetrafluoroethylene composite coatings with a dense structure, which presents excellent anti‐wear properties and corrosion resistance.